Interesting case of acute pancreatitis secondary to leptospirosis - Mundkur, Suneel C.; Reddy, Niharika; Moras, Karen Janice; George, Divya Mary; Pereira, Rochelle Anne (International Journal of Contemporary Pediatrics, 2023)
Leptospirosis caused by Leptospira icterohemorrhagica is a severe, acute condition which can be complicated by multi-organ dysfunction renal failure, liver failure (jaundice), acute respiratory distress syndrome, rhabdomyolysis and bleeding manifestations such as petechiae, epistaxis, hematemesis, hemoptysis, malena, commonly we see characteristic conjunctival suffusion and may lead to fatal multiple organ dysfunction. Leptospirosis may be mistaken for diverse infectious diseases such as malaria, dengue fever, rickettsial disease, ehrlichiosis or hantavirus infection which may mimic leptospirosis. We reported an interesting and rare case of leptospirosis with acute pancreatitis who had a prolonged course.